2009
DOI: 10.1590/s0074-02762009000600014
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of human parvovirus B19 among human immunodeficiency virus-infected patients in a medium-sized city in Rio de Janeiro, Brazil

Abstract: Parvovirus B19 (B-19)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
3
5
0
3
Order By: Relevance
“…In this study, evaluating the seroprevalence and B19V DNA positivity among blood donors in the Southern part of Brazil we found 53.9% B19V IgG seroprevalence and 1.9% positivity of B19V DNA. The detected seroprevalence was similar to the seroprevalences obtained for blood donors in other Brazilian regions like the São Paulo state (60%), and in HIV‐positive individuals (62%) from Rio de Janeiro . It was also observed that the seroprevalence increased over the age (ie, 42.8% in blood donors of 17‐29 years to 65.5% in donors of >40 years).…”
Section: Discussionsupporting
confidence: 82%
“…In this study, evaluating the seroprevalence and B19V DNA positivity among blood donors in the Southern part of Brazil we found 53.9% B19V IgG seroprevalence and 1.9% positivity of B19V DNA. The detected seroprevalence was similar to the seroprevalences obtained for blood donors in other Brazilian regions like the São Paulo state (60%), and in HIV‐positive individuals (62%) from Rio de Janeiro . It was also observed that the seroprevalence increased over the age (ie, 42.8% in blood donors of 17‐29 years to 65.5% in donors of >40 years).…”
Section: Discussionsupporting
confidence: 82%
“…However, with the introduction of highly active antiretroviral treatment (HAART), recent studies have shown low number of cases with anemia caused by B19 in HIV infected patients [de Azevedo et al, ; Pereira et al, ]. Several studies have reported that almost 30% of HIV infected patients have no IgG antibodies against B19 and are at risk of developing B19 infection, persistent viremia and chronic anemia [Azevedo et al, ]. B19 IgG negative patients are at risk for primary infection whereas IgG positive immunocompromised patients may be considered at risk of both reinfection with another genotype or reactivation of a B19 persistent infection according to few studies [Weiland et al, ; Bremner et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the importance of B19V infection in the HAART era, a study to estimate the frequency of B19V seroconversion in a cohort of HIV-infected patients was conducted by our group during an eight-year period (2001-2008) at the Infectious Diseases Department of Antonio Pedro University Hospital (HUAP) at the Fluminense Federal University (Niterói, state of Rio de Janeiro, Brazil) (de Azevedo et al 2009). Seroconversions were detected in approximately 30% (28 of 88) of our anti-B19 IgG-negative patients, a similar proportion to that found by others (Chernak et al 1995, Mylonakis et al 1999).…”
mentioning
confidence: 99%